Perceptions of and experiences with police and the justice system among the Black and Indigenous populations in Canada - Cotter, Adam (Juristat, 2022)
Perceptions of and experiences with police and the justice system among the Black and Indigenous populations in Canada: Highlights * The Black population and Indigenous people (First Nations people, Métis, and Inuit) living in Canada have distinct histories, backgrounds, geographic distributions, and current conditions and situations. While these groups are distinct, their perceptions and experiences are explored in this article to highlight similarities and differences relative to the population who is neither Indigenous nor a member of a population group designated as visible minority. * According to the 2020 General Social Survey (GSS) on Social Identity, one in five Black (21%) and Indigenous (22%) people have little or no confidence in police, double the proportion among those who were neither Indigenous nor a visible minority (11 %). * Based on data from the 2019 GSS on Canadians' Safety (Victimization), Black and Indigenous people are more likely to rate police performance poorly. Perceptions of and experiences with police and the justice system among the Black and Indigenous populations in Canada by Adam Cotter, Canadian Centre for Justice and Community Safety Statistics The Canadian Charter of Rights and Freedoms (Canada Act 1982) states that all individuals in Canada are equal before and under the law, and that all should be afforded equal protection and benefit of the law without discrimination. [...]over 200 different ethnic or cultural origins were cited by those who self-identified as Black in the 2016 Census of population, with the 10 most frequent being Jamaican, Other African,3 Haitian, Canadian, English, Somali, Nigerian, French, Ethiopian and Scottish (Statistics Canada 2019).